Comprehensive assessment of the quality of flour wheat-flax composite mixtures for the production of enriched bread - N. A. Revyakina; N. V. Sokol (Новые технологии, 2023)
In the modern world there are constant large-scale changes that indicate the need for the development and launching new food products to meet the body's needs for energy and nutrients, since most products on the food market are unbalanced in the main food components. To fortify food products, non-traditional types of raw materials are used. The study and use of various composite mixtures of wheat and flax flour in bread technology will make it possible to enrich finished products with nutrients, ensure the required level of rheological characteristics when kneading dough and obtain high-quality products.The purpose of the research was to study wheat-flax composite mixtures according to a set of quality indicators characterizing baking properties.The objects of the study were wheat-flax composite mixtures with different dosages of flax flour (2.5; 5.0; 7.5; 10%) to the weight of the flour mixture. A sample containing 100% of premium wheat flour was taken as a control sample. The study of the rheological properties of composite mixtures was carried out using a farinograph device. Bread baking was carried out using the test laboratory baking method.It was found that composite mixtures containing flaxseed flour of 5.0 and 7.5% by weight of the flour mixture had quality indicators that contribute to the formation of the rheological properties of the dough throughout the entire technological process, that are necessary for the production of highquality finished products.The obtained data can be used in designing recipes for enriched bakery products and developing innovative technologies in the bakery industry.